2021
DOI: 10.1038/s41598-021-93191-y
|View full text |Cite
|
Sign up to set email alerts
|

Eight months follow-up study on pulmonary function, lung radiographic, and related physiological characteristics in COVID-19 survivors

Abstract: To describe the long-term health outcomes of patients with COVID-19 and investigate the potential risk factors. Clinical data during hospitalization and at a mean (SD) day of 249 (15) days after discharge from 40 survivors with confirmed COVID-19 (including 25 severe cases) were collected and analyzed retrospectively. At follow-up, severe cases had higher incidences of persistent symptoms, DLCO impairment, and higher abnormal CT score as compared with mild cases. CT score at follow-up was positively correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 38 publications
7
45
1
1
Order By: Relevance
“…Lesions of COVID-19 induced pneumonia were distributed mainly in the subpleural region and progressed from patches to large patches with hardly noticeable pleural changes. With the progression of the disease, density changes were seen with a regular pattern of GGO-consolidation-GGO, which was aligned with previous reports ( 26 28 ). The pathological findings revealed that edema, proteinaceous exudate, and hyperplasia of pneumocytes with patchy inflammatory cellular infiltration and the absence of hyaline membranes were histological changes in the early stage of COVID-19 which presented as GGOs at the onset ( 26 , 29 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lesions of COVID-19 induced pneumonia were distributed mainly in the subpleural region and progressed from patches to large patches with hardly noticeable pleural changes. With the progression of the disease, density changes were seen with a regular pattern of GGO-consolidation-GGO, which was aligned with previous reports ( 26 28 ). The pathological findings revealed that edema, proteinaceous exudate, and hyperplasia of pneumocytes with patchy inflammatory cellular infiltration and the absence of hyaline membranes were histological changes in the early stage of COVID-19 which presented as GGOs at the onset ( 26 , 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…There were no patients with mild type recruited in this study. Patients in the severe group were older than those in the non-severe group (50.63 ± 13.29 vs. 42.89 ± 13.27 years old, respectively, p = 0.001) and were hospitalized for 23.5 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) days, longer than the hospitalization duration of non-severe patients [18 (15-23) days, p < 0.001]. Severe patients were more likely to have severe symptoms at onset.…”
Section: Clinical Characteristicsmentioning
confidence: 96%
“…This is consistent with data that shows that 12 months after COVID-19 values of spirometry and bodyplethysmography were <LLN in less than 10% of patients (except for a reduction of TLC in 42%), independently from the severity of the disease during inpatient treatment (WHO guideline severity scale) [40,67]. When assessed up to 8 months after hospitalization, some studies reported a significant relationship between the current functional impairment and the previous severity of the disease [25,29,31,33,36,37,66,68], while others did not [24,26,63,69]. The situation is complicated by a potential interplay between persistent symptoms and functional alterations that could be promoted by changes in behavior, for example regarding physical capacity or anxiety and depression.…”
Section: Discussionsupporting
confidence: 87%
“…We also found the symptom burden not to be related to characteristics of the previous hospital stay, particularly the severity of COVID-19, which goes along with data from shorter follow-up times in previous studies [36,61,[63][64][65]. In some studies, however, a positive correlation between the severity of the COVID-19 disease and the symptom burden at follow-up had been found [15,26,35,58,60,66]. This heterogeneity could be due to different classifications of disease severity or not yet specified subtypes of the virus or the fact that studies employed different tools, such as personal interview, phone interview and online survey.…”
Section: Discussionsupporting
confidence: 84%
“…Since COVID-19 is primarily a respiratory infection, it can be anticipated that continued pulmonary opacities picked up on thoracic radiography render such individuals susceptible to experience residual respiratory symptoms. The lingering opacities may be indicative of fibrosis that some of the patients with COVID-19 pneumonia go on to develop [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%